Discovery of potential inhibitor against human acetylcholinesterase: a molecular docking and molecular dynamics investigation. (June 2017) - Singh, Surya Pratap; Gupta, Dwijendra
Graphical abstract: Highlights: Virtual screening of library of compounds against human AChE. MD simulation and PCA based analysis of ligand interaction with hAChE. Free energy based analysis of binding affinity of ligand. Abstract: Alzheimer's disease (AD) is a progressive neurodegenerative disease of central nervous system among elderly people. Human acetylcholinesterase (hAChE), an important enzyme in neuronal signaling, is responsible for the degradation of acetylcholine which in turn prevents the post synaptic signal transmissions. hAChE has been an attractive target of drug discovery for the search of therapeutics against AD. In the recent past hAChE has become hot target for the investigation of new potential therapeutics. We performed virtual screening of entire database against hAChE. Further, the extra precision molecular docking was carried out to refine the docking results and the best complex was passed for molecular dynamics simulations in order of understanding the hAChE dynamics and its behavior in complex with the ligand which corroborate the outcomes of virtual screening. This also provides binding free energy data that establishes the ligands efficiency for inhibiting hAChE. The computational findings discussed in this paper provide initial information of inhibitory effects of ligand, (drugbank entry DB00983), over hAChE.